1949
DOI: 10.1021/ie50478a042
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Density Isotherms for Sodium Sulfate–Ethylene Glycol–Water

Abstract: Solubilities and saturated solution densities are reported at intervals of 5°from 25°to 100°C. for sodium sulfate in aqueous ethylene glycol solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1952
1952
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 3 publications
2
13
0
Order By: Relevance
“…Thompson and coauthors reported that the weight percent of Na 2 SO 4 in saturated EG solution was only 0.487%. 62 Because of the similarity between DEG and EG, we can conclude that Na 2 SO 4 is likely not very soluble in DEG either. Furthermore, we found that the excellent quality of Pd decahedra was produced after the DEG solution was saturated with Na 2 SO 4 , as shown in Figure 1A.…”
Section: àmentioning
confidence: 99%
“…Thompson and coauthors reported that the weight percent of Na 2 SO 4 in saturated EG solution was only 0.487%. 62 Because of the similarity between DEG and EG, we can conclude that Na 2 SO 4 is likely not very soluble in DEG either. Furthermore, we found that the excellent quality of Pd decahedra was produced after the DEG solution was saturated with Na 2 SO 4 , as shown in Figure 1A.…”
Section: àmentioning
confidence: 99%
“…The minimum is not observed in e.g. NaCl-MEG-H2O 34 or Na2SO4-MEG-H2O 35 , where the bond must be different apparently. The reproducibility of the density measurements are listed in Table 2, Table 3, Table 4, and Table 5.…”
Section: Resultsmentioning
confidence: 86%
“…The minimum observed in this system is also very different from similar mixed solvent salt systems. The minimum is not observed in, for example, NaCl−MEG−H 2 O 34 or Na 2 SO 4 − MEG−H 2 O, 35 where the bond must be different apparently.…”
Section: Resultsmentioning
confidence: 95%
“…The principle lies in the fact that the slope of the heating or cooling curve of the system of known composition undergoes a relatively abrupt change at the saturation temperature (or cloud point). Thus, the general procedure is to observe the rate of cooling (or heating) of the system under a constant thermal head as a function of time (108,184,235). Refined techniques for obtaining such data and utilizing them to derive precise transition temperatures have been developed in recent years at the National Bureau of Standards (84,139,225) for use in meltingpoint determinations, but the methods are equally applicable to solubility studies.…”
Section: Methods Of Cooling and Heating Curvesmentioning
confidence: 99%
“…Circulating arrangement making use of differences in specific gravity by the isosystic method it is often desirable to precede the actual measurement by a cycle of heating to achieve complete solution, followed by rapid cooling to precipitate the solute in a finely divided state (19). In some types of work, such as solubilization studies, it is sometimes necessary to keep the amount of solid solute used at the lowest level feasible to minimize unwanted adsorption effects (142), while in others (e.g., solubility of various hydrates) it is necessary that the system be kept seeded with traces of the particular solute form in question in order to avoid supersaturation errors (235).…”
Section: Saturation Equilibriummentioning
confidence: 99%